Trafficking (in) Representations: Understanding the recurring appeal of victimhood and slavery in neoliberal times - Andrijasevic, Rutvica; Mai, Nicola (Anti-Trafficking Review, 2016)
Representations of trafficking and forced labour are pervasive within media, policymaking, and humanitarian debates, discourses and interventions. The terms exploitation and trafficking are increasingly used to characterise the work that migrants do in the sex industry and other irregular employment sectors. Of late, the notion of ‘modern slavery’ is on show in campaigns aiming to raise awareness about trafficking and funds for anti-trafficking initiatives among corporations and local enterprises as well as the general public. Celebrity interventions, militant documentaries, artistic works and fiction films have all become powerful vectors of the global distribution of the trafficking and ‘modern slavery’ rhetoric. These offer simplistic solutions to complex issues without challenging the structural and causal factors of inequality. Through fictional and narrow representations of ideal victims they tend to entrench racialised narratives and conflate all sex work with trafficking, which legitimates criminalising policies and interventions exacerbating the social vulnerability of sex workers. It is because of the under-researched role of representation in the development of anti-trafficking policies and initiatives that the Anti-Trafficking Review decided to devote a thematic issue on trafficking representations.